(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study examines the strategic deployment of mythonyms in J.K. Rowling’s Harry Potter series, analyzing how these nomenclatural choices function as instruments of characterization, foreshadowing, and world-building. Through close textual analysis of character names, locations, and magical entities, this research demonstrates that mythonyms operate simultaneously on multiple semantic levels, creating intertextual dialogues with classical, medieval, and folkloric traditions while establishing internal narrative coherence. The findings reveal that Rowling’s mythonymic system draws predominantly from Greco-Roman mythology, Arthurian legend, Celtic folklore, and alchemical tradition, creating a sophisticated onomastic network that reinforces themes of destiny, moral duality, and the cyclical nature of heroism. This analysis contributes to broader discussions of literary onomastics and demonstrates how mythonyms function as compressed narrative information, encoding character traits, plot trajectories, and thematic concerns within nominal structures. The study concludes that mythonyms represent a critical yet underexamined dimension of literary craft, particularly within fantasy literature, where world-building demands the creation of culturally resonant yet imaginatively distinct nominal systems.